CTA in 1999: Responding to demand, establishing new partnerships - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
In his introduction to the CTA Annual Report for 1999, the then Director, Dr R D Cooke, lays great emphasis on 'the need to ensure that information services are demand-driven', alongside the 'the need to increase support for localised, or...